Pengaruh Pembelajaran Qur’a N Three In One Terhadap (Prestasi Akademik, Hubungan Sosial Santri, Dan Masyarakat) Di Pondok C.E.O - Rahmad Saleh Lubis; Sedya Sentosa (CV. ITTC INDONESIA, 2023)
Rahmad Saleh Lubis, 20204012012. The Effect of Three In One Qur'an Learning on Academic Achievement, Santri Social Relations, and Society) At Pondok C.E.O. Thesis, Master of Islamic Education Study Program Faculty of Tarbiyah and Teacher Training UIN Sunan Kalijaga Yogyakarta, 2022 The background of this research is the Qur'an as a guide for humans, the holy book that is used as a way of life for Muslims in the world. Reading the Qur'an over and over again does not only improve the work of the brain, but can calm the heart and soul so that it makes the reader calm. The separator between truth and evil, is not just bullshit. Whoever abandons the Qur'an because of his pride, Allah will destroy him. Whoever asks for guidance from anything other than the Qur'an, Allah will mislead him.The purpose of this study was to determine how the concept and influence of the three in one Al-Quran learning model, namely on academic achievement, social relations of students, and society. Knowing how to implement the three-in-one Al Qur’an learning model, namely academic achievement, social relations between students, and the community. Knowing what factors support and hinder the implementation of the three-in-one Al Qur’an learning model. The research location is precisely at Pondok C.E.O Bogor which is located at Jl. Situdaun, Cinangneng Village, Bogor.The results showed 1) Implementation of Three In One Qur'an Learning was carried out because it was one of the simple and systematic methods to be used as teaching materials for students, in learning starting from the reading stage, after feeling fluent in terms of reading, tajwid was taught alternately and give each other corrections to the reading of the Koran between students, 2) Supporting factors and inhibiting the implementation of three in one Qur'an learning, namely the first supporting factors, in terms of the three in one Qur'an learning process, the Ustadz has good potential and have the shahadah to teach the Qur'an. As for the obstacle, namely the lack of interest of students in participating in learning activities of the Qur'an, 3) The results of the t test show the sig value for the effect of learning the Qur'an three in one (X) on the academic achievement of students (Y) is 0.000 <0.05 , and the value of tcount > ttable is 2,326 > 2,048. So learning the Qur'an three in one has a significant effect on the academic achievement of Pondok C.E.O . students